2014
DOI: 10.1186/1471-2431-14-209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pediatric first aid training on preschool teachers: a longitudinal cohort study in China

Abstract: BackgroundUnintentional injuries are a major cause of death among children. Data suggest that the retention of knowledge and skills about first aid declined over time. The purpose of this study was to assess the effects of pediatric first aid training among teachers.MethodsA stratified random sampling method was used to select 1,067 teachers. The selected trainees received pediatric first aid training. Follow-up assessments were conducted 6 months, 9 months and 4 years following the training. A standardized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
(43 reference statements)
1
23
0
14
Order By: Relevance
“…Their results demonstrated that the training significantly improves knowledge levels toward first aid among respondents who attended the training course. [29] Regarding first aid skills, the present study results revealed that many incorrect practices were prevalent among respondents and the most of them had inadequate performance related to first aid. Meanwhile after implementation school teachers acquired good first aid practices with statistical significant difference pre and post intervention.…”
Section: Discussionmentioning
confidence: 57%
“…Their results demonstrated that the training significantly improves knowledge levels toward first aid among respondents who attended the training course. [29] Regarding first aid skills, the present study results revealed that many incorrect practices were prevalent among respondents and the most of them had inadequate performance related to first aid. Meanwhile after implementation school teachers acquired good first aid practices with statistical significant difference pre and post intervention.…”
Section: Discussionmentioning
confidence: 57%
“…Among the six articles that were part of the sample, five were published in English [12][13][14][15][16] and one in Portuguese [17]. Among the countries where the studies were conducted are China, United States, Wales and Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in China investigating the knowledge of teachers six months, nine months, and four years after conducting a training on pediatric first aid procedures concluded that, despite their decreased knowledge, overtime the educational intervention improved the apprehension of knowledge on a short-term and long-term basis. (5) In view of the effectiveness of training programs on first aid procedures for teachers this study highlights the importance of conducting further studies contributing to the education in health for such professionals.…”
Section: Introductionmentioning
confidence: 94%